INNV-22. TO TREAT OR NOT TO TREAT – TREATMENT OUTCOMES OF VERY ELDERLY GLIOBLASTOMA PATIENTS. (11th November 2019) - Baumgarten, Peter; Prange, Georg; Harter, Patrick; Forster, Marie-Therese; Wagner, Marlies; Steinbach, Joachim; Seifert, Volker; Senft, Christian
Abstract: OBJECTIVE: The prognosis especially of older patients with glioblastoma is poor. Novel therapies are usually reserved for patients ≤65 years. As the population is growing older, the challenge remains as to how very elderly patients ≥75 years should be treated. Only limited outcome data exist for this patient subgroup. METHODS: Between 2010 and 2018 we treated a total of 977 patients with glioblastoma at our institution. Of these, 144 patients were ≥75 years at diagnosis. The primary procedure was surgery or biopsy followed by adjuvant treatment, if possible. We retrospectively investigated progression-free and overall survival (OS) and looked at potential prognostic factors influencing survival, including Karnofsky performance score (KPS), surgical therapy, adjuvant therapy as well as MGMT promoter methylation status. RESULTS: In our very elderly cohort, the median age was 79 years (range: 75–110). Biopsy only was performed in 108 patients, resection was performed in 36 patients. Median OS for the entire cohort was 5.9 months. Patients without adjuvant treatment fared worse than patients receiving either radiotherapy and/or chemotherapy (1.2 vs. 8.4 months, p< 0.001). Multivariate analysis showed that KPS at presentation (≥70 vs. ≤60), surgery vs. biopsy, and MGMT status (methylated vs. non-methylated) were significantly associated with OS (6.3 vs. 3.9 months, p=0.002; 12.6 vs. 4.9 months, p=0.003; and 10.5 vs. 5.0 months, p=0.009, respectively). CONCLUSION: For patients with glioblastoma ≥75 years, the natural course of the disease is devastating, and there is a negative treatment bias in these patients. Very elderly patients, too, benefit from multimodal treatment including microsurgical tumor removal. Treatment options and outcomes should be thoughtfully discussed with patients before treatment decisions are made.